Seasonal Variation in Fibrinogen in the Rotterdam Study - Bom, J G van der; Maat, M P M de; Bots, M L; Hofman, A; Kluft, C; Grobbee, D E (Thrombosis and Haemostasis, 1997)
As evidence accumulates to implicate fibrinogen as a risk indicator for cardiovascular disease, it is of interest to study its seasonal variation. A population based cross-sectional study was performed among participants of the Rotterdam Study, a cohort of 7,983 men and women, aged 55 years and over. Fibrinogen levels were measured by the prothrombin time derived method in the first 2,325 participants of the study. Fibrinogen levels were considerably higher in winter. The seasonal difference was 0.34 g/1 (95% confidence interval 0.29,0.39) and was more pronounced in subjects aged 75 years and over than in subjects aged 55 to 75 years, 0.43 g/1 (0.34,0.52) and 0.29 g/1 (0.24,0.35), respectively. Additional adjustment for body mass index, systolic and diastolic blood pressure, and total and HDL cholesterol did not materially change the findings. After adjustment for seasons, outdoor temperature was not associated with fibrinogen. Adjustment for outdoor temperature did not change the seasonal variation of fibrinogen, seasonal difference 0.31 g/1 (0.24, 0.37). In conclusion, fibrinogen levels are highest in Winter. The seasonal variation of fibrinogen is more pronounced in the elderly. Outdoor temperature does not seem to play a role in the seasonal variation of fibrinogen. Seasonal variation of fibrinogen may partly explain the increased cardiovascular disease mortality in Winter.